2023
DOI: 10.1186/s13019-023-02276-4
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT imaging of giant primary pulmonary meningioma: a case report and literature review

Abstract: Background An ectopic meningioma, such as a primary pulmonary meningioma (PPM), is a rare type of tumor that primarily originates outside of the central nervous system. The most common presentation of PPM is isolated pulmonary nodules or masses, and most of them are benign. Only sporadic cases have been reported. This case reported a giant primary pulmonary meningioma and systematically reviewed previously reported cases in the literature. Case presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Meningiomas occurring in tissues and organs not covered by the meninges are termed ectopic meningiomas. PPM is defined as a primary meningioma in the lung tissue[ 3 ] and is classified as a rare condition under the category of lung tumors of ectopic tissues according to the World Health Organization (WHO) Classification of Thoracic Tumors[ 4 ].…”
Section: Clinical Features Of Ppm and Mpmnmentioning
confidence: 99%
See 4 more Smart Citations
“…Meningiomas occurring in tissues and organs not covered by the meninges are termed ectopic meningiomas. PPM is defined as a primary meningioma in the lung tissue[ 3 ] and is classified as a rare condition under the category of lung tumors of ectopic tissues according to the World Health Organization (WHO) Classification of Thoracic Tumors[ 4 ].…”
Section: Clinical Features Of Ppm and Mpmnmentioning
confidence: 99%
“…It has also been suggested that a conservative approach, using close medical monitoring, is the best option for patients when the location, size, and number of smaller nodules challenge the accessibility for biopsy or resection[ 13 , 15 ]. Malignant PPMs are prone to recurrence or metastasis, leading to a poor prognosis[ 3 , 16 , 17 ]. Conversely, some reports have indicated that the prognosis of patients with malignant PPM is actually favorable owing to a typically slow progression[ 6 ].…”
Section: Clinical Features Of Ppm and Mpmnmentioning
confidence: 99%
See 3 more Smart Citations